Family-Based Corruption Prevention through Pesantren Values - Arifin, Samsul; Baharun, Mokhammad; Saputra, Rahmat (UIN Maulana Malik Ibrahim Malang, 2021)
Pesantren (Islamic boarding school) has a great potential for family-based corruption prevention. This study aims to determine the values of pesantren and portraits of sakinah family personalities in the texts of “Zadu Az-Zaujayn” and “Syair Madura” in relation to the prevention of corruption. It uses an ethnographic-hermeneutic qualitative approach. The research concludes that the value of pesantren associated with the prevention of corruption lies in the expression